A large-scale multimodal investigation of the interplay between the serotonergic system and emotion processing - Manfred Klöbl; Matej Murgaš; Murray Bruce Reed; Leo Robert Silberbauer; Annette M. Hartmann; Godber Mathis Godbersen; Gregor Gryglewski; Lukas Nics; Andreas Hahn; Dan Rujescu; Marcus Hacker; Rupert Lanzenberger (Translational Psychiatry)
Abstract Considering the complexity of serotonergic influence on emotions, we conducted a comprehensive investigation of the interplay between emotion processing and the serotonergic system using simultaneous functional and molecular neuroimaging during pharmacological challenge while disentangling the effects of serotonin transporter (SERT) binding, genotype, and diagnosis of major depressive disorder (MDD). Herein, 153 subjects (44 with MDD) performed a facial emotion processing task during functional magnetic resonance imaging (fMRI) before and after an acute intravenous application of 8 mg citalopram or placebo. Patients with MDD were assessed again after at least three months of antidepressant treatment. Citalopram administration resulted in a reduced fMRI activation in regions involved in fear processing, including the anterior cingulate cortex (ACC), when viewing fearful faces contrasted against happy or neutral faces. ACC activation correlated negatively with striatal/thalamic SERT availability across drug conditions as measured by [11 C]DASB positron emission tomography. Across groups, citalopram-induced changes in ACC activation correlated with emotional attribution, indicating stronger reductions for subjects with higher self- versus other- attribution. Moreover, striatal SERT availability mediated the influence of the number of 5-HTTLPR/rs25531 LA alleles on ACC activation under placebo. Patients with MDD exhibited increased activations in the intraparietal and superior frontal sulcus in response to fearful versus happy faces at baseline, and along the parieto-occipital/calcarine fissure after treatment. We interpret our findings on multiple levels of the serotonergic-emotional interaction within the context of enhanced passive coping and acute anxiolytic effects of citalopram following potential changes in serotonin or SERT availability.